Enhanced Cyber Resilience Solution by Threat Detection using IBM Cloud Object Storage System and IBM QRadar SIEM - Storage, IBM (IBM Redbooks, 2021)
This Solution Redpaper™ publication explains how the features of IBM Cloud® Object Storage System reduces the effect of incidents on business data when combined with log analysis, deep inspection, and detection of threats that IBM QRadar SIEM provides. This paper also demonstrates how to integrate IBM Cloud Object Storage's access logs with IBM QRadar SIEM. An administrator can monitor, inspect, detect, and derive insights for identifying potential threats to the data that is stored on IBM Cloud Object Storage. Also, IBM QRadar SIEM can proactively trigger cyber resiliency workflow in IBM Cloud Object Storage remotely to protect the data based on threat detection. This publication is intended for chief technology officers, solution and security architects, and systems administrators.